(untitled) (International Journal of Financial, Administrative and Economic Sciences, 2024)
This study aims to investigate the impact of large shareholders’ ownership on the financial performance of listed companies in the Saudi market. The study was conducted on a sample of 158 listed companies over the period 2016-2022, using the panel data method. While the study documents that there is a significant positive relationship between the size of large shareholders’ ownership and firm’s financial performance, this relationship turns to be negative if the large shareholders own large stakes in more than one firms in the market. Further investigation reveals that the negative relation between a firm’s financial performance and the ownership of large shareholders is attributed to those shareholders who own a large stake in the same industry of the focal firm but not those who have large stakes in other firms in different industry. The findings of the study provide practical implications for policy makers. Firms; board, and investors in the financial markets. Additionally, this study contributes to the existing literature by showing there is heterogeneity in the effect of large shareholders’ ownership on firms’ policies.